Structure elucidation, immunomodulatory activity, antitumor activity and its molecular mechanism of a novel polysaccharide from Boletus reticulatus Schaeff - Siyuan Su; Xiang Ding; Yiling Hou; Binbin Liu; Zhouhe Du; Junfeng Liu (Food Science and Human Wellness)
A new water-soluble heteropolysaccharide with a molecular weight of 15 kDa was isolated from the fruiting bodies of Boletus reticulatus Schaeff. Structural characterization results revealed that B. reticulatus Schaeff polysaccharide (BRS-X) had a backbone of 1,6-linked α-D-galactose and 1,2,6-linked α-D-galactose which branches were mainly composed of a terminal 4-linked β-D-glucose and the ratio of D-galactose and D-glucose was 5:1. Bioactivity assays indicated that BRS-X displayed a strong proliferative activity in T cells and B cells and promoted the secretion of immunoglobulin G (IgG), IgE, IgD and IgM. In addition, BRS-X could facilitate the proliferation and phagocytosis of RAW264.7 cells and could significantly inhibit the growth of tumors in S180-bearing mice. The results of transcriptome sequencing analysis illustrated that total 46 genes enriched in MAPK and total 34 genes enriched in PI3K/Akt signaling pathways in BRS-X group. The protein VEGF and VEGFR expression were significantly reduced under the treatment with BRS-X. These findings provide a scientific basis for the edible and medicinal value of BRS-X.